If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(3x+5)=3(6x+1)
We move all terms to the left:
2(3x+5)-(3(6x+1))=0
We multiply parentheses
6x-(3(6x+1))+10=0
We calculate terms in parentheses: -(3(6x+1)), so:We get rid of parentheses
3(6x+1)
We multiply parentheses
18x+3
Back to the equation:
-(18x+3)
6x-18x-3+10=0
We add all the numbers together, and all the variables
-12x+7=0
We move all terms containing x to the left, all other terms to the right
-12x=-7
x=-7/-12
x=7/12
| 36x+-7=137 | | 2x+3=4x—1 | | 3x-1=18.5 | | 27x+5=86 | | 4(x-1)-3=4 | | 8c-5=3c+25 | | 5(5z-3)-9(3z-2)=2 | | x^2-12x+144=108 | | 10x=171−9x | | F=9/5c+98 | | (3x+2)*(3x+2)=0 | | 11x-1=5x+23 | | 2y-3/y+3=5/7 | | (x+1)(x-2)=x*x+2 | | (3h-4)(3h-4)(9h-12)=3993 | | (4/7)^9+(4/7)^2=(4/7)^2p-1 | | (4/7)^9+(4/7)^2=(4/7)^(2p-1) | | 5y+2=2y+1/2y | | (8x+20x)(10x-5x)=10 | | 3x+12=13.68 | | 5x^2+8x-208=0 | | 13-3/4x=7 | | 7x^2+x=4x^2-1 | | 7x+11=2x+26= | | 7+4x6=X | | 3-4n=25 | | 2z-z=-2 | | 5(x+5)-(x+6)=x+60 | | 8(x-3)=3(2-2x) | | 2(+4m+6=4(5m+6)m | | 7x+6-3x-4=26 | | 21/x=41/1/3 |